Evaluation of Input and Process in the Implementation of Online Poetry Appreciation Learning - Cintya Nurika Irma; Cerianing Putri Pratiwi (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aimed to describe and analyze the evaluation of input and process in online poetry appreciation learning at senior high schools in Purworejo Regency. Evaluation is an essential part of the learning process, serving as a reflection on the achievement of learning objectives. Methodology: This study employed a program evaluation research approach using the Stufflebeam evaluation model, focusing on input and process evaluation. Data collection techniques included both interactive and non-interactive methods. The interactive analysis components involved data reduction, data display, and conclusion drawing. Main Findings: The input evaluation revealed that: a) some students did not own personal technological devices, experienced internet quota limitations, lacked deep media and digital literacy learning, and had limited access to translated poetry e-books, b) there was a need to improve teachers’ pedagogical and professional competence standards, and c) The school had implemented several relevant programs, including tablet loan programs, internet quota aid, school domain email creation, IT team formation, periodic training on the use of learning devices and social media, counseling support by guidance and counseling teachers, and the establishment of a digital library. Novelty/Originality of this study: This study contributes valuable insights into the alignment between input and process in poetry appreciation learning, tailored to the characteristics of the schools involved.